Impact of partition: refugees in Pakistan: struggle for empowerment and states's response - Hassan, Amtul (Colombo, 2006)
Book Summary of Impact Of Partition:refugees In Pakistan:struggle For Empowerment And State`s Response This volume deals primarily with the experience of partition refugees in Pakistan. Issues like partition carnage, pangs of displacement, the challenges of resettlement and the deliberate policy of the state and ruling elites to disempower the Muhajirs and their reassertion as a political force constitute some of the major areas of concern for this study. The meteoric rise of the MQM as a political power an d its campaigns against feudalism, sardari system, intelligence agencies, as well as terrorism and religious parties have been dealt with in this work.
Keywords: Refugees-Pakistan